Direction of Trade Statistics, December 2017. (Direction of Trade Statistics; Direction of Trade Statistics ;, 2017)
This paper outlines data that are estimated for all partners. In the absence of some or all of the monthly Direction of Trade Statistics (DOTS), quarterly or annual reported DOTS is used. Annual reported data to the UN COMTRADE database are treated as reported to the IMF. When only annual or quarterly data are available, the monthly trade between country A and B is distributed over the relevant months using the following information (in order of priority): the monthly value of the partner trade reported by country B; the monthly total value of imports and exports reported in the IMF's International Financial Statistics (IFS) by country A; or the monthly value of trade that all other partner countries have reported with country A for the specific month. The monthly distribution is done through a time-series procedure that reproduces at the best the month-to-month changes of the information available at the monthly level and, simultaneously, produces estimates that are consistent with quarterly or annual data reported by countries. Estimates are computed for months, and then quarterly and annual totals are obtained by summation.